Dielectric relaxation of water: assessing the impact of localized modes, translational diffusion, and collective dynamics. Issue 37 (15th September 2021) - Hölzl, Christoph; Forbert, Harald; Marx, Dominik
Abstract : The dielectric relaxation spectrum of water can be quantitatively reproduced by ab initio molecular dynamics simulations. Its decomposition into auto- and crosscorrelation terms suggests that fits of experimental spectra may require revision. Abstract : A multitude of distinct physical processes and molecular mechanisms have been introduced in the past in an effort to understand the unusual dielectric loss spectrum of water with its pronounced peak at roughly 20 GHz. Our computer simulations including ab initio molecular dynamics provide no evidence for a major impact of cage dynamics or local-diffusive motion on the lineshape below 200 GHz. We also show that the collective motion of hundreds of water molecules and/or their significant diffusive displacements are not required. Instead, the dielectric relaxation of water up to about 200 GHz can be quantitatively described in terms of two unimodal and smoothly decaying spectral contributions.